2015
DOI: 10.5120/19928-2069
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Techniques for the Diagnosis of Lung Cancer with ANT Colony Optimization

Abstract: Lung cancer is the leading cause of cancer-related death in the worldwide. The prognosis is poor, with less than 15% of patients surviving 5 years after diagnosis. The poor prognosis is attributable to lack of efficient diagnostic methods for early detection and lack of successful treatment metastatic disease. However, persons with early lung cancer have lower lung cancer-related mortality than those with extensive disease, suggesting early detection and treatment of lung cancer might be beneficial. Computer T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Z. Zubi et al (2014) extracted features from chest x ray images and used concept of back propagation neural network method to improve the accuracy [ 31 ]. Rashmee Kohad et al (2015) used ant colony optimization with ANN and SVM to predict the accuracy of 98% and 93.2% respectively on 250 lung cancer CT images [ 16 ]. Kourou et al (2015) outlined a review of various machine learning approach on several cancer data and concluded that application of integration of feature selection and classifier will provide a promising result in analysis of cancer data [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Z. Zubi et al (2014) extracted features from chest x ray images and used concept of back propagation neural network method to improve the accuracy [ 31 ]. Rashmee Kohad et al (2015) used ant colony optimization with ANN and SVM to predict the accuracy of 98% and 93.2% respectively on 250 lung cancer CT images [ 16 ]. Kourou et al (2015) outlined a review of various machine learning approach on several cancer data and concluded that application of integration of feature selection and classifier will provide a promising result in analysis of cancer data [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…ANN based lung cancer detection system has been established and utilized first order texture features extracted from CT images [11]. Significant texture features yielded a better accuracy of 98.4% using ANN compared to 93.2 % by SVM [12]. Classification using Hop field neural network achieved 98% accuracy in detecting lung cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are various doctors and researchers have done in the field of lung cancer diagnosis and achieved better solution to find out better results. According to the World Health Organization (WHO) [1] approximately 14 million new cases and 8.2 million cancers related death in 2012. According to American Lung Association, deaths due to Lung cancer is more than the next most common cancers combined (colon, breast and pancreatic).…”
Section: Introductionmentioning
confidence: 99%
“…S. P. Tidke, et al [3] have suggested SVM algorithm to diagnosis of lung cancer disease and achieved satisfactory accuracy. R. Kohad et al [1] have used classifiers like SVM and ANN and proposed ACO_ANN. The proposed algorithm gives better accuracy which higher than the accuracy compare to others.…”
Section: Introductionmentioning
confidence: 99%